PENERAPAN MANAJEMEN BERBASIS MADRASAH DALAM MENINGKATKAN MUTU PEMBELAJARAN DI MADRASAH TSANAWIYAH NEGERI 1 KABUPATEN SOLOK SELATAN - Agusrial Hendrika (UNISAN JURNAL, 2024)
Education is an important aspect in the development of a nation. Madrasah Tsanawiyah Negeri (MTsN) 1 South Solok Regency as an Islamic education institution at the secondary level has a very vital role in forming character and preparing students to become competent individuals. One of the key factors in improving the quality of education at MTsN 1 South Solok Regency is the implementation of madrasa-based management. Madrasah-based management emphasizes effective and efficient management based on the characteristics and needs of the madrasah itself. By implementing madrasa-based management, it is hoped that the quality of learning at MTsN 1 South Solok Regency can be improved significantly. This research aims to examine the current condition of the quality of learning at MTsN 1 South Solok Regency, the factors that are obstacles to improving the quality of learning, and how the implementation of madrasa-based management can improve the quality of learning at the madrasa. A qualitative approach with case study research was used in this research. The data collection techniques used were observation, interviews and documentation studies. Data analysis was carried out using descriptive analysis techniques. The results of the research show that the condition of the quality of learning at MTsN 1 South Solok Regency is currently still facing several challenges, such as lack of involvement of all related parties, lack of accurate and integrated data management, lack of understanding of the concept of madrasa-based management, limited human resources and infrastructure. , as well as the lack of use of technology in learning. However, the implementation of madrasa-based management has great potential to improve the quality of learning in these madrasas. With madrasa-based management, the process of planning, organizing, implementing and controlling learning can be carried out more effectively and efficiently. The conclusion of this research is that concrete steps are needed to overcome existing obstacles and implement madrasa-based management effectively at MTsN 1 South Solok Regency. In this way, it is hoped that the quality of learning at this madrasa can increase, so that it can produce a generation that is qualified and ready to compete in this era of globalization.